The minimizing of fluorescence background in Raman optical activity and Raman spectra of human blood plasma - Tatarkovič, Michal; Synytsya, Alla; Šťovíčková, Lucie; Bunganič, Bohuš; Miškovičová, Michaela; Petruželka, Luboš; Setnička, Vladimír (Analytical and bioanalytical chemistry, 2015)
Raman optical activity (ROA) is inherently sensitive to the secondary structure of biomolecules, which makes it a method of interest for finding new approaches to clinical applications based on blood plasma analysis, for instance the diagnostics of several protein-misfolding diseases. Unfortunately, real blood plasma exhibits strong background fluorescence when excited at 532 nm; hence, measuring the ROA spectra appears to be impossible. Therefore, we established a suitable method using a combination of kinetic quenchers, filtering, photobleaching, and a mathematical correction of residual fluorescence. Our method reduced the background fluorescence approximately by 90%, which allowed speedup for each measurement by an average of 50%. In addition, the signal-to-noise ratio was significantly increased, while the baseline distortion remained low. We assume that our method is suitable for the investigation of human blood plasma by ROA and may lead to the development of a new tool for clinical diagnostics.
Keywords: Spectrum Analysis, Raman; Fluorescence; krevní plazma; Ramanova spektroskopie; optická otáčivost; lidé; Plasma; fluorescence; Humans; Optical Rotation